Hubungan Antara Tingkat Kecemasan dengan Sindrom Dispepsia pada Mahasiswa Fakultas Kedokteran Universitas Muslim Indonesia Angkatan 2023 - Sarah Sarwati, Athiyyah; Wahyu, Sri; Eka Yanti, Andi Kartini; Hidayati, Prema Hapsari; Bakhtiar, Ilma Khaerina (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Patients with dyspepsia syndrome are among the top 10 most common conditions treated in hospitals across Indonesia. Medical students experience mental fatigue, including anxiety, due to the demanding learning process and tight class schedules. This study used a quantitative and qualitative approach with a cross-sectional research design to examine the relationship between anxiety levels and dyspepsia syndrome among the 2023 cohort of medical students at the Faculty of Medicine, University of Muslim Indonesia. The data were obtained from primary data collected through questionnaires filled out by respondents before and after their exams. The chi-square test results showed a p-value of 0.001 (p < 0.05) before the exam, and a p-value of 0.036 (p < 0.05) after the exam, indicating a significant relationship between anxiety levels and dyspepsia syndrome in the 2023 cohort of medical students at the University of Muslim Indonesia. There is a significant relationship between anxiety levels and dyspepsia syndrome in medical students at the University of Muslim Indonesia, both before and after exams. The most common level of anxiety experienced was mild anxiety.